Cardiogenic shock in resource-limited settings - Koolwal, Prateek; Mangal, Kishore (Journal of Nepalese Society of Critical Care Medicine, 2024)
Cardiogenic shock (CS) is a critical condition characterized by severe circulatory failure, leading to inadequate perfusion of organs and high mortality rates, especially in resource-limited settings. In these environments, the management of CS faces numerous challenges, including limited access to advanced medical technologies, inadequate healthcare infrastructure, and a lack of trained personnel. These factors contribute to delayed diagnosis and treatment, exacerbating patient outcomes. Global collaboration between well-resourced and under-resourced regions is essential to improve the management of CS. Such partnerships can facilitate knowledge sharing, capacity building through training programs, and the establishment of standardized treatment protocols tailored to local contexts. Additionally, collaborative research initiatives can enhance understanding of CS across diverse populations, while equitable resource allocation can ensure that life-saving technologies reach those in need. By leveraging the strengths of both well-resourced and under-resourced settings, stakeholders can work towards reducing the mortality associated with cardiogenic shock and improving overall healthcare delivery. Ultimately, fostering a global network focused on innovative solutions and shared best practices will be crucial in addressing the persistent challenges of managing cardiogenic shock in resource-limited settings.